On the evolution of the prefracture zone near the crack tip in a nonlinear anisotropic body - Kaminsky, A.A.; Kurchakov, E.E. (Reports of the National Academy of Sciences of Ukraine, 2018)
A boundary-value problem in terms of the displacement vector components for the equilibrium state of a non linear elastic orthotropic body with a crack of normal separation is stated with regard for its prefracture zone. As a result of the numerical solution of the problem, the evolution of this zone under the loading is shown. The deformation field near the crack tip is studied.